MANAGEMENT OF DA'WAH BY THE PERSAUDARAAN MUSLIMAH (SALIMAH) IN PREVENTING SEXUAL HARASSMENT AMONG TEENAGE GIRLS - Hafizda Ardianti; Muaz Tanjung (International Journal of Cultural and Social Science, 2025)
The purpose of this research is to identify how the da'wahmanagement of the Persaudaraan Muslimah (Salimah)organization prevents sexual harassment among adolescent girlsin the Deli Serdang Regency area. This research was conductedin the Deli Serdang region using a qualitative approach anddescriptive methodology. The results of this study include that theda'wah management at Salimah Deli Serdang plays a veryimportant role in preventing sexual harassment among teenagegirls. The da'wah management carried out by Salimah isstructured by applying the basic principles of management,namely planning, organizing, implementing, and supervising. Andby using religious materials that are relevant to the needs andchallenges faced by teenagers. Programs such as regular studysessions, education on self-protection, and spiritual guidance notonly create a conducive nurturing environment but also enhanceyoung girls' awareness of the importance of maintaining religiousvalues, managing emotions well, and building socialrelationships.